Human Papilloma Viruses and Breast Cancer – Assessment of Causality - Lawson, James Sutherland; Glenn, Wendy K.; Whitaker, Noel James (Frontiers in Oncology, 2016)
High risk human papilloma viruses (HPVs) may have a causal role in some breast cancers. Case control studies, conducted in many different countries, consistently indicate that HPVs are more frequently present in breast cancers as compared to benign breast and normal breast controls (odds ratio 4.02). The assessment of causality of HPVs in breast cancer is difficult because (i) the HPV viral load is extremely low, (ii) HPV infections are common but HPV associated breast cancers are uncommon, (iii) HPV infections may precede the development of breast and other cancers by years or even decades. Further, HPV oncogenesis can be indirect. Despite these difficulties, the emergence of new evidence has made the assessment of HPV causality in breast cancer a practical proposition. With one exception the evidence meets all the conventional criteria for a causal role of HPVs in breast cancer. The exception is “specificity”. HPVs are ubiquitous which is the exact opposite of specificity. An additional reservation is that the prevalence of breast cancer is not increased in immunocompromised patients as is the case with respect to HPV associated cervical cancer. This indicates that HPVs may have an indirect causal influence in breast cancer. Based on the overall evidence, high risk HPVs may have a causal role in some breast cancers.